1976
DOI: 10.1084/jem.143.6.1551
|View full text |Cite
|
Sign up to set email alerts
|

Generation of superoxide anion and chemiluminescence by human monocytes during phagocytosis and on contact with surface-bound immunoglobulin G.

Abstract: Polymorphonuclear neutrophils and monocytes emigrate from the bloodstream to areas of inflammation and play an essential role there in a variety of physiological and pathological events, including defense against infection. Although the biochemical basis for these cells' microbicidal activity is not completely understood, studies primarily with neutrophils indicate that the killing of most organisms depends upon phagocytosis-associated oxidative metabolism. During phagocytosis neutrophils remove oxygen from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(69 citation statements)
references
References 13 publications
9
60
0
Order By: Relevance
“…This suggestion is in accordance with the present finding that neutrophils, whose number declined sharply on elicitation, emitted more intense chemiluminescence when compared with macrophages. In fact, this supports the earlier reports by Johnston et al [29] and Sagone et al [30] that granulocytes are capable of producing a more intense peak of chemiluminescence than monocytes/macrophages. However, in human blood, such differences in peak chemiluminescence have been attributed to differences in their ability to produce hydroxyl radicals [31].…”
Section: Resultssupporting
confidence: 81%
“…This suggestion is in accordance with the present finding that neutrophils, whose number declined sharply on elicitation, emitted more intense chemiluminescence when compared with macrophages. In fact, this supports the earlier reports by Johnston et al [29] and Sagone et al [30] that granulocytes are capable of producing a more intense peak of chemiluminescence than monocytes/macrophages. However, in human blood, such differences in peak chemiluminescence have been attributed to differences in their ability to produce hydroxyl radicals [31].…”
Section: Resultssupporting
confidence: 81%
“…When suiperoxidle di smutitase a(In catalase, which hlad been heated to dlestroy enizymatic activity, were added, no inhibitory effect on cell lysis was ohserved. It wats ascertained that 50 mM miannitol did not (18)(19)(20)(21), annd it is seen from our results that the process of ADCC, phagocytosis, and postphaigocytic events are intimately correlated, allthouigh no ca'usal relation mav be deduced friom these results.…”
Section: Introductionmentioning
confidence: 46%
“…Using a more sensitive and specific fluorometric assay (20) we found that monocytes release _20% of the amount of hydrogen peroxide generated by neutrophils. Several studies indicate that human monocytes also generate superoxide anions during phagocytosis (10,13 These findings may contribute to our understanding of monocyte function. Monocytes kill bacteria less efficiently than PMN (8,9,33).…”
Section: Discussionmentioning
confidence: 99%
“…With various stimulating agents, monocytes produced 20-70% of the chemiluminescence generated by neutrophils. Release of superoxide by monocytes amounted to -60% of the production by PMIN (13).…”
Section: Introductionmentioning
confidence: 99%